"Luvina" o las maromas del hombre aquel que hablaba - Sancho Dobles, Leonardo (2007)
The article presents an approach to one of the possible interpretations of the story "Luvina", written by Mexican author Juan Rulfo, from the perspective of formal analysis of literary pieces.  For this analysis, elements such as structure, space, time and semantic plane are taken into account. The approach to the meaning of the text is further enriched by different intertextual elements that permit establishing a different interpretation of the story.